A novel non-invasive hip traction technique for hip arthroscopy in the below-knee amputation (BKA) patient - Atzmon, Ran (J Hip Preserv Surg, 2017)
Prolonged sitting and mobilizing from a seated position are known to exacerbate the symptoms in patients with hip pathology. For patients who lack mobility and require extended periods of time in seated positions, such as amputees, the symptoms of femeroacetabular impingement can be debilitating and limit their ability to operate a wheelchair, use a prosthetic limb or complete activities of daily living. Hip arthroscopy surgery offers a minimally invasive technique to treat hip pathology but requires hip distraction to facilitate instrument maneuverability. Invasive methods of hip distraction have been previously described for use in amputees for hip arthroscopy. We herein describe a non-invasive surgical technique for hip distraction in the below-knee amputation patient.